A pre- and postpartum study of selected biochemical parameters in ewes for the early detection of pregnancy toxemia - ROUBIES (Ν. ΡΟΥΜΠΙΕΣ), N.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S.; MINAS (Α. ΜΗΝΑΣ), A.; PAPASTERIADIS (ΑΧ. ΠΑΠΑΣΤΕΡΙΑΔΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
A field investigation on the incidence of subclinical ovine ketosis was performed in two large sheep flocks in an agricultural region of central Greece. Sixty - four animals were allocated in 2 study groups: group C, consisted of 29 non-pregnant females and group S of 35 end-term pregnant ewes. The trial lasted 6 weeks, including the immediate pre- and postpartal period. Blood samples were collected on weekly intervals and used for determining the concentrations of ß-hydroxybutyrate (BHB), acetoacetate (AcAc), glucose, total (TB) and conjugated (CB) bilirubin, calcium (Ca), inorganic phosphorus (P), sodium (Na), potassium (K), magnesium (Mg) and the activity of sorbitol dehydrogenase (SDH) and γ-glutamyl transferase (yGT). All the animals remained clinically healthy throughout the trial and parturition was uneventful. Eighteen group S ewes (51.4%) delivered 1 lamb, 12 (34,3%) twins, 4 (11.4%) triplets and 1 (2.9%) 4 lambs. Although the overall evaluation of the biochemical analysis did not support the existence of subclinical ketosis, blood glucose remained significantly lower (P<0.05) in group S sheep, with its lowest value (2.3±0.34 mmol/1) recorded 1 week prior to parturition. Sporadic cases of subclinical hyperketonemia may occur, despite optimal flock management.